20-Hydroxyeicosatetraenoic Acid Is a Key Mediator of Angiotensin II–induced Apoptosis in Cardiac Myocytes. Issue 1 (July 2015) - Zhao, Huiying; Qi, Guohua; Han, Yong; Shen, Xin; Yao, Fanrong; Xuan, Chengluan; Gu, Yan; Qian, Steven Y.; Zeng, Qinghua; O'Rourke, Stephen T.; Sun, Chengwen
Abstract : Abstract: Cardiomyocyte apoptosis is involved in a variety of cardiac stresses, including ischemia-reperfusion injury, heart failure, and cardiomyopathy. Both Angiotensin II (Ang II) and 20-hydroxyeicosatetraenoic acid (20-HETE) induce apoptosis in cardiomyocytes. Here, we examined the relationship between 20-HETE and Ang II in cardiomyocyte apoptosis. Apoptosis was examined using flow cytometry in primary cultured rat cardiomyocytes treated with control, Ang II, and Ang II plus HET0016 (a 20-HETE formation inhibitor). The results demonstrated that the treatment of cardiomyocytes with Ang II or 20-HETE significantly increased the percentage of apoptotic cells and that Ang II-induced apoptosis was markedly attenuated by HET0016 or losartan (an AT1 receptor antagonist). In apoptotic mechanism experiments, Ang II or 20-HETE treatment significantly reduced mitochondrial membrane potential, indicating that a mitochondria-dependent mechanism is involved. Ang II-induced alteration in mitochondrial membrane potential was significantly attenuated by HET0016. Treatment of cardiomyocytes with Ang II also increased superoxide production, and this effect of Ang II was attenuated by HET0016. Treatment of cardiomyocytes with Ang II significantly increased CYP4A1 expression and 20-HETE production, as measured by Western blot, real-time RT-PCR, and mass spectrometric analysis. All results suggest that 20-HETE may play a key role in Ang II-induced apoptosis in cardiomyocytes by a mitochondrial superoxide-dependent pathway.